Factors influencing employee retention of academic home tutors in a private school - Lim Lee Ping; Ong Choon Hee; Tan Owee Kowang; Chi-Hua Wu (Institute of Advanced Engineering and Science, 2024)
This study’s goal is to investigate the links between pay and benefits, worklife balance, professional development, and employee retention among academic home tutors in a Malaysian private school. Data from 80 respondents from this private school were gathered using a quantitative survey method. Statistical package for social science (SPSS) was employed throughout the study to analyze the data. The study results showed that salary & compensation and career enhancement positively correlate with employee retention. Meanwhile, work-life balance was not statistically linked with employee retention. The management should revise the human resource management practices by including these elements. The management should design salary & compensation packages that fit with individual knowledge, capabilities, and performance. The management may also consider offering flexible work schedules, such as training, mentoring, job mobility, and a reduction in working hours, as well as wellness assistance, such as counselling services and health and wellness initiatives. This will give employees the chance to advance their careers.